The Art and craft of motion picture editing - Hoggan, Michael B. (New York Routledge, 2022)
"This book explains the broader context of what the art and craft of motion picture editing entails, framing the creative acts of editing within an overall view of the production process and requirements for effective storytelling. This book offers real experiences and advice from seasoned editors on the editing process, providing a detailed examination of filmmaking from the editor's point-of-view and exploring how best to cultivate creative relationships with other areas of production to form the final personality of the film. Emphasizing both practicality and creativity, industry veteran Michael Hoggan successfully bridges the gap between the mechanical skills of editing and the thought process behind these decisions. While most books focus primarily on the mind of the creator, this book explores the evolution of practices in film production and editing with respect to the ever-changing expectations of the audience. As the book demonstrates, understanding editing from the audience's perspective is essential to any successful film. This book will be of interest to postproduction students, independent filmmakers, film critics, and agents with editing clients. It is accompanied by a collection of rich digital materials including a glossary, bibliography, and more"-- Provided by publisher.
Snapshot of the invisible artist -- Motion picture editor and the story -- The motion picture editor/director partnership -- The motion picture editor and the actor's performance -- The motion picture editor and the cinematographer -- Overview of the editing process -- Narratives editing : principles and techniques--film editing "rules" -- Forming the "editor's cut," its creative opportunities -- The motion picture editor and sound design -- The motion picture editor and the audience.
Includes bibliographical references and index.
Keywords: Motion picture editors -- Interviews; Motion pictures -- Editing